Deliberative democracy as a trend in modern theory of democracy: the analysis of the main approaches - A. N. Linde (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2015)
The article deals with the theoretical concept of the problem of deliberative democracy (modern trends in the theory of democracy), examines approaches for the understanding the content of the concept and analyzes understanding of the term «deliberative de-mocracy» by J. Bessett, John. Dewey, Habermas, J. Cohen and B. Ackerman.